Testing metabolic and pharmacological agents for recovery following de novo acute heart failure in an isolated rat heart model - Deshpande, Gaurang (Department of Medicine, 2016)
Acute heart failure is a potentially lethal clinical emergency without any effective therapy. Using an isolated rat heart model, we established and validated a model of de novo acute heart failure to study novel putative cardio protective therapies against acute heart failure, including glucose, insulin and the molecular agent sphingosine-1-phosphate(component of high density lipoprotein) for recovery. In isolated rat hearts, the protocol consisted of three phases: stabilization at normotensive perfusion pressure, hypotensive acute heart failure and recovery by restoring normotension. Low glucose (2.5mM) and high albumin-bound free fatty acids (1.3mM) (±adrenaline 10-M) were added in theperfusate. Molecular and metabolic agents were administered either alone or in combination in the acute heart failure or recovery phases. Effects of glucose, insulin and sphingosine-1-phosphatewere observed on heart function, cell death and mitochondrial respiration. In the absence of adrenaline, combination of glucose andsphingosine-1-phosphateduring acute heart failure improved functional recovery by increasing the heart rate. In the presence of adrenaline, glucose and sphingosine-1-phosphate administered separately were cardioprotective in the recovery phase by improving heart rate. The combination of glucose+insulin and glucose+sphingosine-1-phosphate in the recovery phase also increased heart rate. Glucos9+sphingosine-1-phosphate+insulin increased heart rate and left ventricular developed pressure.Sphingosine-1-phosphate reduced expression of cytochrome C, but metabolic agents had no effect.AG490 (inhibitor of signal transducer and activator of transcription 3) attenuated the cardio protective effect of sphingosine-1-phosphatewithincreased expression of the phosphorylated inactive form of this transcription factor protein. Conclusion: We have established and validated an ex-vivo model of de novoacute heart failure. The combination of metabolic and molecular treatments improved heart function by increasingsinus node activity_ Sphingosine-1-phosphate not only improved heart rate, but also reduced cell death, an effect mediated via activation of signal transducer and activator of transcription 3. Our data provide novel principles and approaches for the treatment of acute heart failure.